IMPLEMENTASI GREEN BUSINESS PRACTICES DAN PENGARUHNYA TERHADAP KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR - Wilana, Wili; Naryoto, Pambuko (Jurnal Review Pendidikan dan Pengajaran, 2024)
This study examines the implementation of green business practices and their impact on the financial performance of manufacturing companies. With the growing global awareness of the importance of environmental sustainability, companies are required to adopt environmentally friendly business practices. This research employs a quantitative method with a survey approach to collect data from 100 manufacturing companies in Indonesia that have implemented green business practices. The data were analyzed using multiple linear regression to test the relationship between the implementation of green business practices and the financial performance of the companies. The results indicate that the implementation of green business practices significantly and positively affects the financial performance of the companies. Factors such as energy efficiency, waste management, and the use of environmentally friendly raw materials contribute significantly to increasing the profitability and competitiveness of the companies. These findings support the view that green business practices are not only beneficial for the environment but also financially advantageous for companies. This research provides practical implications for the management of manufacturing companies in formulating sustainable and environmentally friendly business strategies. Additionally, this study contributes academically to the fields of environmental management and corporate finance by providing empirical evidence on the economic benefits of green business practices.